Qualitative and quantitative analysis of lignicolous macromycetes in different forest associations on the Galičica Mountain - Karadelev, Mitko (Macedonian Journal of Ecology and Environment, 1994)
The occurrence and frequency of lignicolous macromycetes in the most important forest associations and on various hosts in the Galičica Mountain are presented on tables. Most species were collected on Quercus (84) and Fagus (50), since those trees are the most numerous ones in the area investigated. The distribution of fungi in particular forests and on particular tree genera is discussed. Many species are hitherto known in Macedonia only from this area.